Motivating Action and Maintaining Change: The Time‐Varying Role of Homework Following a Brief Couples' Intervention. (12th October 2015) - Hawrilenko, Matt; Eubanks Fleming, C. J.; Goldstein, Alana S.; Cordova, James V.
Abstract : Studies regarding the effectiveness of homework assignments in cognitive‐behavioral treatments have demonstrated mixed results. This study investigated predictors of compliance with homework recommendations and the time‐varying relationship of recommendation completion with treatment response in a brief couples' intervention ( N = 108). More satisfied couples and couples with more motivation to change completed more recommendations, whereas couples with children completed fewer. The association between recommendation completion and treatment response varied with the passage of time, with the strongest effect observed 6 months after the intervention, but no discernible differences at 1 year postintervention. Couples that completed more recommendations experienced more rapid treatment gains, but even those couples doing substantially fewer recommendations ultimately realized equivalent treatment effects, although they progressed more slowly. Implications are discussed.